2011
DOI: 10.1016/j.enbuild.2011.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty analysis in building performance simulation for design support

Abstract: Building Performance Simulation (BPS) has the potential to provide relevant design information by indicating directions for design solutions or uncertainty and sensitivity analysis. A major challenge in simulation tools is how to deal with difficulties through large variety of parameters and complexity of factors such as non-linearity, discreteness, and uncertainty. It is hypothesized that conducting an uncertainty and sensitivity analysis throughout key stages of the design process would be of great importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
277
0
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 423 publications
(288 citation statements)
references
References 14 publications
2
277
0
9
Order By: Relevance
“…Uncertainties in scenario conditions are very different from physical and design uncertainties in the sense that they can change during the building's life time [19]. Taking scenario uncertainties into account is relevant to design decision support, in particular when considering the design robustness and (future) adaptability of a building.…”
Section: (I) Limiting the Risk By Controlling The Scenario Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainties in scenario conditions are very different from physical and design uncertainties in the sense that they can change during the building's life time [19]. Taking scenario uncertainties into account is relevant to design decision support, in particular when considering the design robustness and (future) adaptability of a building.…”
Section: (I) Limiting the Risk By Controlling The Scenario Uncertaintiesmentioning
confidence: 99%
“…The material properties are identical for both options and therefore not explained in more detail. For more information please refer to [19].…”
Section: Design Option 2: Heating/ Cooling Storagementioning
confidence: 99%
“…Furthermore, in many analyses or designs the explicit evaluation of the result for different scenarios -be they defined based on user behaviour, economic parameters, climate change, ... -may be wanted as suggested by Hopfe and Hensen [15]. This asks for the formulation and application of Monte Carlo multi-layered uncertainty schemes.…”
Section: Paper Objectivesmentioning
confidence: 99%
“…come from domain experts in building physics. More recently, Hopfe and Hensen [87] analyzed energy performance (energy consumption and thermal comfort) and considered three different groups of uncertainties for building design: (i) physical uncertainties inherent in physical properties, which appear in quantified measurements; (ii) design uncertainties, such as changes in the room geometry or the window size; (iii) scenario uncertainties that are linked to building usage. The results of their study confirmed the added value and usefulness of integrating uncertainty analysis in building performance simulations [87].…”
Section: Uncertainty and Imprecisionmentioning
confidence: 99%